Exegese mítica das cartas do jesuíta Fernão Cardim - Gutierrez, Silas (2015)
This work studies the christian jewish myth as a discursive element that gives meaning and value Fernão Cardim letters. Through the studies proposed by Mircea Eliade (2000, 2000a, 2010, 2011, 2012, 2013) and the research conducted by the Bakhtin Circle (1975,1981,1997,2003, 2009), we see how the myth made up by language, creates realities and projects the reader for a supersensible plan. One of the main points of Eliade's studies is to question how the myth or mythical resonances interpose in the lives of human beings in their daily lives, and the religious phenomenon, in the author's opinion, is realized through images and symbols in a mythical context, for a specific type of language because religious symbolism refers to the deeper aspects of life and experience of human being in relation to the world. In our research, we notice that the Colonial Brazil is described mainly as a majestic spatiality; the jesuit creates, as an accomplished painter, a splendid environment and evokes the beauty of nature. Finally, we find that the myth is a way of being of language covering senses regulatory processes; these are related to subjects historically situated in places and different times in relation or not to the same enterprise enunciation. Thence, it follows that the christian jewish myth, seen as an ideological sign, is filled with meaning and purpose, it can be the representation, the ordering and systematization of historical and material relations of a given society